Parity, Interpregnancy Interval, and Socioeconomic Status in Relation to Low Birth Weight: A Prospective Cohort in Yogyakarta - Rina Oktasari; Hadi Riyadi; Ali Khomsan; Katrin Roosita; Yulin Lestari (Media Publikasi Cendekia Indonesia, 2026)
Low birth weight (LBW, <2,500 g) remains a critical public health problem, contributing to neonatal mortality and long-term risk of non-communicable diseases, and national estimates in Indonesia indicate a prevalence ranging from approximately 6.2% to 11.7%. Parity and interpregnancy interval (IPI) are important reproductive determinants of perinatal outcomes, and their effects may be modified by socioeconomic status (SES). This study aimed to investigate the association between parity and IPI with LBW and to assess whether SES modifies these associations in a prospective cohort of pregnant women in Yogyakarta, Indonesia. A total of 120 women (poor households n=48; non-poor households n=72) were recruited purposively from community health centers and a maternity hospital/clinic. Inclusion criteria were gestational age 26–35 weeks, maternal age 20–35 years, parity 1–2, non-smoker, and provision of informed consent. Pre-pregnancy BMI was obtained through maternal recall of the last measured height and weight before conception. Data were analyzed using Pearson’s χ² tests for baseline comparisons and stratified logistic regression models to estimate adjusted odds ratios (aORs) with 95% confidence intervals. The prevalence of LBW was higher among women with non-optimal IPI (<24 or >60 months and primigravida) compared to those with optimal IPI (24–60 months). Multiparity showed a protective tendency against LBW, particularly among non-poor women. SES significantly modified the association between IPI and LBW (p for interaction <0.05). These findings suggest that multiparity may reduce LBW risk, whereas non-optimal IPI increases it, with SES acting as an effect modifier. Strengthening preconception counseling on birth spacing and targeted support for low-SES families are warranted